The Extent of Organizational Dynamic Capabilities' Contribution to Human Talent Management: An Analytical Study of the Opinions of a Sample of Administrative Leaders in the Presidency of the University of Mosul. - داغر, حلا فازع (Journal of Economics and Administrative Sciences, 2020)
The recognition of the dynamic organizational capabilities in their actual and influential extent in the work environment achieves a set of positive data that can fall under the addition axes, particularly with regard to the organization's ability to manage human talents in them, so the researchers sought to identify the level of contribution of dynamic organizational capabilities in the management of human talents in terms of Keep them away in the research organization by indicating the level of relationship and impact between them. The presidency of Mosul University was chosen as a field for the current study, and data were collected by adopting the questionnaire form as the main tool for the study. The study used a deliberate sample of (42) administrative leaders in the investigated organization and adopted a number of tools (arithmetical mean, standard deviation, the ratio of the response to the scale area, coefficient of variation, correlation coefficient, and linear regression) under the statistical software (SPPS). The results of the research confirm the existence of a degree of the actual contribution of organizational dynamic capabilities to of human talents management in the investigated organization, and this was confirmed by the results of the correlation and impact between the variables, The research also presented a number of recommendations, the most prominent of which is the need for the senior administrations of the investigated organization to mobilize their supportive capabilities towards enhancing the level of organizational dynamic capabilities in order to manage human talents by adopting an approach that enables them to manage them efficiently and effectively.